Applying the Health Belief Model to predict preference for surgical intervention versus medical therapy among patients with open-angle glaucoma - Khaled Awad; Ramy Awad; Hager Elkazaz; Marwa Saleh; Azza Mehanna (BMJ Open Ophthalmology, 2022)
Objective To determine the factors influencing patient preference of surgical intervention versus medical therapy for open-angle glaucoma based on the Health Belief Model.Methods and analysis The study is a cross-sectional study. The study was conducted on 309 patients having open-angle glaucoma attending glaucoma clinic at Alexandria Ophthalmology Hospital, Alexandria, Egypt. The patients were subjected to an interview questionnaire comprising demographic data, patient knowledge and beliefs about glaucoma, glaucoma medications and treatment options, and patient preference of treatment modality, based on the Health Belief Model.Results About half of the patients (46%) were found to prefer surgical intervention. Patients were less knowledgeable about glaucoma, in general, but knowledge scores of patients preferring surgical intervention were significantly higher than those preferring medical therapy (Percentage Mean Score, PMS: 42.46%–37.37%, respectively). Male and female patients using more medications were significantly more likely to prefer surgical intervention (p=0.015 and p=0.003, respectively). Patients having preference for surgical intervention reported higher scores for perceived susceptibility and severity of long-term medical therapy (PMS=72.61% vs 54.62%–68.62% versus 52.83%, respectively), higher scores for perceived benefits of surgical intervention (PMS=92.90% vs 43.96%, respectively) and higher scores for self-efficacy (PMS=97.18% vs 50.37%, respectively). Meanwhile, they obtained lower scores for perceived barriers to surgical intervention (PMS=53.43% vs 86.07%, respectively).Conclusions Male gender, increased number of used eye-drops and more knowledge about glaucoma were significantly associated with patient preference for surgical intervention. Perceived benefits and barriers and self-efficacy were the significant predictors for patient surgical interference preference.